The apartheid censors' responses to the works of Frantz Fanon, Amilcar Cabral and Steve "Bantu" Biko - Ross, Tamlyn Sue (Stellenbosch : Stellenbosch University, 2013)
Thesis (MA)--Stellenbosch University, 2013.